Chest Wall Deformities - Saxena, Amulya K. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This comprehensive work offers detailed state of the art information on the changing paradigms in the evaluation, diagnosis, clinical investigation, and treatment of chest wall deformities. The chapters reflect the shift towards conservative and minimal access treatment options, and the combination of concise descriptions and high-quality images provide the reader with a clear understanding of all relevant concepts. Diagnostic and imaging modalities are analysed in depth, and surgical procedures are explained step by step with the aid of clear, informative illustrations. Experts in the management of chest wall deformities from all over the world have contributed their experiences and approaches, making Chest Wall Deformities a unique book in the field and an ideal reference work for clinicians and surgeons.
Keywords: Medicine.; Radiology.; Surgery.; Pediatric surgery.; elektronické knihy; electronic books